If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(t + -3) + -3(t + -2) = t + 8 Reorder the terms: 2(-3 + t) + -3(t + -2) = t + 8 (-3 * 2 + t * 2) + -3(t + -2) = t + 8 (-6 + 2t) + -3(t + -2) = t + 8 Reorder the terms: -6 + 2t + -3(-2 + t) = t + 8 -6 + 2t + (-2 * -3 + t * -3) = t + 8 -6 + 2t + (6 + -3t) = t + 8 Reorder the terms: -6 + 6 + 2t + -3t = t + 8 Combine like terms: -6 + 6 = 0 0 + 2t + -3t = t + 8 2t + -3t = t + 8 Combine like terms: 2t + -3t = -1t -1t = t + 8 Reorder the terms: -1t = 8 + t Solving -1t = 8 + t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-1t' to each side of the equation. -1t + -1t = 8 + t + -1t Combine like terms: -1t + -1t = -2t -2t = 8 + t + -1t Combine like terms: t + -1t = 0 -2t = 8 + 0 -2t = 8 Divide each side by '-2'. t = -4 Simplifying t = -4
| 7x^2+23x+6= | | 0.7x^2-4.2x-0.7=0 | | 2x^2+11x+5= | | 3x^2+16x+5= | | 7x^2+32x+16= | | 86-4x=32x+22 | | 2x^2-11x+5= | | 12-10x=212-45x | | 2x+5=-25-8x | | 13x+12x+3=12 | | 7x^2-8x+1= | | 3l+80=5l | | 4x-2=11x-65 | | 5x+30=12x-26 | | 6x^3-4x^2+8x+2= | | 7p^2+8p+1=0 | | x+2=95+x | | 0.5(8a+6)=42 | | 7b+6=-22 | | x^2-18x=19 | | x^2=57 | | 4(2x-3)=5x+7 | | 10y+7z= | | 5x(x-3)=(x+4)(x+3)(x+3) | | 3(x-2a)+2b=x-a | | y+4/5=30 | | -55+z=100 | | -77=-1t+55 | | 0.75x^2-0.5=0 | | 7(2x-4)=224 | | x^2+6x+58=0 | | 2(3t-2)-t=12-t |